Security 2.0 dealing with global wicked problems - Hauss, Charles (Peace and security in the 21st century series, 2015)
When first mentioned in 1994, the concept of human security represented a significant first step in understanding that security dilemmas could no longer be seen as purely geopolitical phenomena that revolve around the nation-state. This book explains the progress made toward human security since then and the steps that remain to be taken.